Kajian Hubungan antara Desain Kendaraan MPV dan Penggunanya di Kota Bandung - Slamet Riyadi; Yannes Martinus Pasaribu; Andar Bagus Sriwarno (Journal of Visual Art and Design, 2013)
Currently motored vehicle has become a necessity for most urban people because the demands of high mobility are performing in their daily activities. Geographical conditions, cultural distinctiveness, economic and lifestyle differences also influence the behavior of its people. Indonesia is a country with a high rate of car sales for multipurpose vehicle (MPV). With this phenomenon, criteria for the Indonesian people about MPV car, with both design aspects and also engineering aspects are no longer controlled by the principal industry in Japan, but should further reflect the desires of consumers in Indonesia. This becomes the basis of the considerations in choosing which vehicle they want to buy. The goal of this research is to identify the factors that influence the occurrence of the difference between consumer choices with a design that has been offered by the manufactures. This study was conducted to prove the hypothesis that car design using ideal values from Japanese country as the main producer of cars in some cases do not have high hopes of being accepted by the Indonesian market, considering several values and cultural differences between ideal values of Japanese car manufactures and conditions of Indonesian people, which resulted in differences of perceptions, between the ideal concept of car design of urban people in Indonesia and the concept that manufactures has offered.